ANALISIS PENERAPAN APLIKASI CORETAX DALAM PROSES ADMINISTRASI PERPAJAKAN DI BALAI BESAR PENGUJIAN MINERAL DAN BATUBARA (BBPMB) TEKMIRA KOTA BANDUNG - Renti Mahtopani; Yusni Nuryani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
.This study aims to analyze the implementation of the CoreTax application in the tax administration process at the Balai Besar Pengujian Mineral dan Batubara (BBPMB) tekMIRA in Bandung. The background of this research is the increasing demand for digital-based tax administration systems to improve efficiency, data accuracy, and integration of tax management in government institutions. This study uses a descriptive qualitative approach. Data were collected through interviews, observations, and documentation involving employees in the finance and tax administration divisions who directly use the CoreTax system. The findings indicate that the implementation of CoreTax contributes to improving the efficiency of tax administration by reducing manual processes, minimizing the use of physical documents, and accelerating tax reporting procedures. The system also supports better data accuracy through digital recording and validation features and enables the integration of tax data into a centralized platform. However, several challenges were identified, including system errors, unstable network access, and limited user understanding of certain application features. These challenges indicate that although CoreTax has significant potential to improve tax administration performance, optimization of system stability and user competence is still required. The findings provide practical implications for improving digital tax administration systems in government institutions.